Investigation of Single and Multiple Effects of Lactic Acid, Cetylpyridinium Chloride and Trisodium Phosphate on the Chicken Carcasses Contaminated with E. coli O157:H7 and Listeria monocytogenes - Yalcin, Halil; Arslan, Ali (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
The study was conducted to investigate the effects of cetylpyridinium chloride (CPC), trisodium phosphate (TSP), lactic acid (LA) and their combinations on survival of E. coli O157:H7 and L. monocytogenes on broiler carcasses. Broiler carcasses were contaminated with 5-strains of E. coli O157:H7 and 10-strains of L. monocytogenes. Then, the carcasses were subjected to decontamination treatments with 0.2% or 0.4 CPC, 8% or 12% TSP, 2% or 4 LA, 2% LA + 8% TSP, 0.2% CPC + 2% LA or 0.2% CPC + 8% TSP at 20 degrees C for 15 min. Effects of treatments on survival of the pathogens were determined. The differences in levels of both pathogens between before and after were significant (P < 0.05). The most effective decontaminant on E. coli O157:H7 was 0.4% CPC with reduction 3.36 log(10) cfu/ml and the least effective decontaminant 2% LA with reduction of 1.91 log(10) cfu/ml. The most effective decontaminant on L. monocytogenes was 0.4% CPC with reduction 5.04 log(10) cfu/ml and the least effective decontaminant 2% LA with reduction of 1.84 log(10) cfu/ml. As a result, the most effective decontaminant against E. coli O157:H7 and L. monocytogenes on chicken carcasses was found to be CPC followed by TSP and LA.
Escherichia coli O157:H7 ve listeria monocytogenes i?le kontamine edilmiş broyler karkaslarında laktik asit, cetylpyridinium chloride ve trisodyum fosfat'ın tekil ve kombine etkilerinin i?ncelenmesi
Keywords: Broiler carcasses; Cetylpyridinium chloride; Trisodium phosphate; Lactic acid; E. coli O157:H7; L. monocytogenes